A study on the application of different stabilizers on soils for earth blocks - Dinopol, Charisse Alexia S.; Cartajenas, Ken Alexis S. (2017)
Soil as a building material, is free and naturally available. Historical success of earth construction has been evident in many countries around the world. There are transitions and innovations of earth blocks as building construction over the years. Many studies conducted experiments of earth blocks that includes the Interlocking compressed Earth Blocks (ICEB) as an alternative building construction especially on low cost housing. In the current industry hollow blocks are the most common blocks use in constructions, but the source of sand limits the material. General Santos City is endowed with rich different characteristics of soil, and a typhoon-free climate. This study examined four particular soil characteristics within General Santos City, Philippines as a possible soil characteristics in producing a hollow earth blocks; all of which belong to four soil series, namely: Makar soil series, Magsaysay soil series, Buayan soil series and Quilada soil series with soil characteristics of Loam soil, coarse, sand, silt soil, and clay soil respectively. Samples of four soil types were mixed with three different binders, cement, lime and fly-ash, with three different ratios to produce hollow earth blocks. The binder ratios are 1:6(14.29%), 1:8(11.11%), 1:10(9.09%). There were n=3 blocks produced per soil type combined per binder ratio, for a total of 108 samples for the four soil characteristics mixed to three different binders individually. These samples were observed and assessed based on appearance, texture, dimensions, shape, and shrinkage. Experiments on the hollow earth block samples conducted through test on dry compressive strength test and water absorption. Results on dry compressive strength showed that of all binders, cement performs best on four different soil characteristic, next is the lime and hollow earth block with higher cement content had better performance. Moreover, results on water absorption showed that hollow earth blocks with higher clay content and less binder had fast water absorption. In terms of soil characteristic, dry compressive strength results showed that clay soil characteristic performs best, on the other hand earth blocks of silt soil characteristic had the poorest performance. Improvement of hollow earth block design as well as research on its material properties are recommended through investigation on stabilizers, studies on other soil textures, and further analysis on soil particles.
Thesis (BS Architecture) -- University of the Philippines Mindanao, 2017